Millennium Development Goals 4 and 5: Progress in the Least Developed Countries of Asia - Rodríguez Martín, José Antonio; Jiménez Aguilera, Juan de Dios; Salinas Fernández, José Antonio; Martín Martín, José María (Social Indicators Research, 2017)
The aim of this study is to propose a territorial measure of maternal and child health in the least developed countries of Asia based on the criteria established in the United Nations Millennium Development Goals 4 and 5 , in a context in which international progress between countries has been uneven up to 2013. Pena's DP2 method is used to compose a synthetic indicator of MDGs 4 and 5 levels for 2013, the last year for which data are available. The index includes information on different variables defined in the Millennium Declaration, as well as a study of the impact of each individual indicator on the outcome of the synthetic indicator of MDGs 4 and 5 levels, and enables classification of these countries in terms of these variables.
Keywords: least developed countries of Asia; maternal and child health disparities; millennium development goals; post-2015 agenda; synthetic indicators; JCR; Scopus